Intelligent color changing packaging film based on esterified starch and black rice anthocyanins - Wei Song; Nan Wu; Yikai He; Huaixiang Zhao; Jian Xu; Lili Ren (Food Chemistry: X)
Intelligent packaging film has received more and more attention because it can help consumers obtain more intuitive information about the packaging, provide better preservation and advanced convenience. In this study, black rice anthocyanin (BRA) was added into composite film formed by starch (S) and esterified starch (ES). As the BRA content increased, the thickness and the total color difference of the S/ES-BRA film increased. The opacity of S/ES-BRA film decreased relative to that of the film without BRA, but increased with the increase of anthocyanin. Compared with S/ES film, the elongation at break of S/ES-BRA0.5 film increased from 33.1 % to 45.4 %, and the tensile strength decreased from 7.3 to 5.8 MPa. S/ES-BRA film had response to different pH values and underwent color changes in different buffer solutions. Intelligent color changing packaging film will used to monitor food quality, water quality and soil properties.